2023
DOI: 10.1021/acsami.2c22646
|View full text |Cite
|
Sign up to set email alerts
|

Designing Interfacial Reactions for Nanometer-Scale Surface Patterning of PDMS with Controlled Elastic Modulus

Abstract: Control over the surface chemistry of elastomers such as polydimethylsiloxane (PDMS) is important for many applications. However, achieving nanostructured chemical control on amorphous material interfaces below the length scale of substrate heterogeneity is not straightforward, and can be particularly difficult to decouple from changes in network structure that are required for certain applications (e.g., variation of elastic modulus for cell culture). We have recently reported a new method for precisely struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Previously, we have shown that the sPDA layers on HOPG can be transferred to soft materials including PDMS , and hydrogels, , taking advantage of the cross-linking reactions used to solidify the bulk polymer (Figure a). For instance, in polyacrylamide (PAAm) hydrogel cross-linking, the free radical polymerization reaction can utilize the PDA as a reactant, which creates a covalent linkage between the PAAm and the sPDA layer.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that the sPDA layers on HOPG can be transferred to soft materials including PDMS , and hydrogels, , taking advantage of the cross-linking reactions used to solidify the bulk polymer (Figure a). For instance, in polyacrylamide (PAAm) hydrogel cross-linking, the free radical polymerization reaction can utilize the PDA as a reactant, which creates a covalent linkage between the PAAm and the sPDA layer.…”
Section: Resultsmentioning
confidence: 99%